Analisa Kinerja Biaya Green Pada Bangunan Utama Flour Mill Plant Berbasis Value Engineering Dan Life Cycle Cost Analysis - Albert Eddy Husin; Iwan Kurniawan (Departemen Teknik Infrastruktur Sipil Institut Teknologi Sepuluh Nopember Surabaya, 2023)
In accordance with the mission of the Suistainebale Development Goals 2030, that by 2030 the new building will have a green concept of 100% and an excising building of 60%. With the Value Engineering and Life Cycle Cost Analysis methods, the application of the green concept to the Main Building of the Flour Mill Plant is used for analysis using Structural Equation Modelling – Part Least Square (SEM-PLS). The result of this study is that there are